Do efficiency gains really translate into more budget for health? An assessment framework and country applications. Issue 8 (14th April 2021) - Barroy, Hélène; Cylus, Jonathan; Patcharanarumol, Walaiporn; Novignon, Jacob; Evetovits, Tamás; Gupta, Sanjeev
Abstract: Efficiency has historically been considered a key mechanism to increase the amount of available revenues to the health sector, enabling countries to expand services and benefits to progress towards universal health coverage (UHC). Country experience indicates, however, that efficiency gains do not automatically translate into greater budget for health, to additional revenues for the sector. This article proposes a framework to assess whether and how efficiency interventions are likely to increase budgetary space in health systems Based on a review of the literature and country experiences, we suggest three enabling conditions that must be met in order to transform efficiency gains into budgetary gains for health. First there must be well-defined efficiency interventions that target health system inputs, implemented over a medium-term time frame. Second, efficiency interventions must generate financial gains that are quantifiable either pre- or post-intervention. Third, public financial management systems must allow those gains to be kept within the health sector and repurposed towards priority health needs. When these conditions are not met, efficiency gains do not lead to more budgetary space for health. Rather, the gains may instead result in budget cuts that can be detrimental to health systems' outputs and ultimately disincentivize further attempts to improve efficiency in the sector. The framework, when applied, offers an opportunity for policymakers to reconcile efficiency and budget expansion goals in health.